2003
DOI: 10.1111/j.1471-4159.2004.02149.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of proline residues in the expression and function of the human noradrenaline transporter

Abstract: The aim was to investigate the roles of proline residues in extracellular loop 2 (P172, P183, P188 and P209) and transmembrane domains 2, 5, 11 and 12 (P108, P270, P526, P551, P552 and P570) in determining noradrenaline transporter (NET) expression and function. Mutants of human NET with these residues mutated to alanine were pharmacologically characterized. Mutation of P108, P270 and P526 disrupted cell surface expression, from [3H]nisoxetine binding and confocal microscopy data. Mutations of P526, P551 and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…As V max of NE transport is dependent on the number of functional NET transporters, we estimated the number of NET transporters inserted in the plasma membrane of transfected cells by determining NE-sensitive binding of [ 3 H]NIS to intact cells at 4°C. This method has also been used in previous studies and by other groups Paczkowski et al 2002;Sucic et al 2002;Paczkowski and Bryan-Lluka 2004), and Blakely and coworkers have confirmed its utility by parallel biotinylation analysis of surface transporters in hNET transfected HEK293 cells (Apparsundaram et al 1998b). This method is based on the assumption that NE competes with nisoxetine binding exclusively at the cell surface since at 4°C NE should not enter the cells by transport and diffusion should be very small.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As V max of NE transport is dependent on the number of functional NET transporters, we estimated the number of NET transporters inserted in the plasma membrane of transfected cells by determining NE-sensitive binding of [ 3 H]NIS to intact cells at 4°C. This method has also been used in previous studies and by other groups Paczkowski et al 2002;Sucic et al 2002;Paczkowski and Bryan-Lluka 2004), and Blakely and coworkers have confirmed its utility by parallel biotinylation analysis of surface transporters in hNET transfected HEK293 cells (Apparsundaram et al 1998b). This method is based on the assumption that NE competes with nisoxetine binding exclusively at the cell surface since at 4°C NE should not enter the cells by transport and diffusion should be very small.…”
Section: Discussionmentioning
confidence: 84%
“…2002; Sucic et al . 2002; Paczkowski and Bryan‐Lluka 2004), and Blakely and coworkers have confirmed its utility by parallel biotinylation analysis of surface transporters in hNET transfected HEK293 cells (Apparsundaram et al . 1998b).…”
Section: Discussionmentioning
confidence: 94%
“…Proline residues play important structural and functional roles in transporters. They can form conformational switches in TM ␣-helices that enable the changes critical for substrate translocation (Sansom, 1992;Paczkowski and Bryan-Lluka, 2004). Because initial mutation of Pro290 did not significantly decrease transport activity, we can conclude that the presence of proline at this position is not strictly required.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies with mammalian dopamine transporters suggested structural as well as functional importance of TM prolines in plasma membrane targeting, assembly, membrane insertion and contribution to dopamine recognition (29). Prolines in the human noradrenaline transporter are involved in assembly of the transporter, inhibitor binding as well as in conformational changes associated with substrate translocation (30). Prolines are also required for cell surface expression and targeting in various membrane proteins (31).…”
Section: Discussionmentioning
confidence: 99%